Replication Report: Did Unconventional Interventions Unfreeze the Credit Market? - Mattia Coppo; Shijia Luo; Francisco Vazquez (Institute for Replication (I4R), 2024)
Tong and Wei (2020) study the impact of unconventional monetary interventions on credit markets during the 2008 global financial crisis. They find that stock prices increase on intervention days, particularly for firms operating in sectors perceived to be more reliant on external funding. Moreover, they report a positive effect of unconventional interventions on firms' subsequent investment, employment, and R&D expenditure, and find that bank recapitalizations are more effective than other interventions. We replicated the reported findings using the data and programs provided by the authors. However, the results did not hold when using the Rajan-Zingales (1998) metric of firms' external financing needs for capital expenditure-one of the two liquidity measures proposed by Tong and Wei (2020). Furthermore, the results do not hold for U.S. and European firms, and they appear driven by a small subset of Canadian firms operating in the extraction of gold and silver ore. These findings raise questions on the results and policy implications proposed in the original paper.
Keywords: 330